Peran Kepemimpinan Kepala Sekolah Terhadap Disiplin Guru Di SMPs Tautiah Arongan - Dahlia; Nur Akmal; Nurlela Kandi; Muhammad Hamra; Khadijah; Desy Safariani; Zahara (Sociale : Journal of Social Science, 2026)
This study aims to analyze the role of school leadership in improving teacher discipline at SMPS Tauthiah Arongan and to identify the efforts undertaken by the principal to foster teacher discipline. This study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The results showed that the principal played an important role in improving teacher discipline through the implementation of mutually agreed-upon regulations, supervision, and direct guidance. Teachers who demonstrated a lack of discipline were provided with direction and guidance through personal meetings and family-oriented warnings. This approach was implemented to foster teachers' professional awareness without prioritizing rigid formal sanctions. The findings indicate that the principal's communicative and humanistic leadership helped maintain a harmonious school environment while encouraging improved teacher discipline. Therefore, school leadership plays an important role in building a culture of discipline and enhancing teachers' professional responsibility at SMPS Tauthiah Arongan.